Hepatic IR and IGF1R signaling govern distinct metabolic and carcinogenic processes upon PTEN deficiency in the liver - Monika Gjorgjieva; Nicolas Calo; Cyril Sobolewski; Dorothea Portius; Jean-Luc Pitetti; Flavien Berthou; Anne-Sophie Ay; Marion Peyrou; Lucie Bourgoin; Christine Maeder; Margot Fournier; Marta Correia de Sousa; et al. (JHEP Reports)
Background & Aims: Hepatocyte-specific deficiency of the phosphatase and tensin homolog (PTEN) triggers steatosis and the development of hepatic tumors. The hepatoprotective effect of PTEN may partly depend on its ability to block insulin receptor (IR) and insulin-like growth factor 1 receptor (IGF1R) signaling. This study aimed to evaluate the individual/combined contributions of IR and IGF1R to hepatic metabolism and tumorigenesis induced by PTEN deficiency. Methods: Mouse models with hepatocyte-specific deletions of Insr, Igf1r, or both, in addition to Pten, were used to investigate the distinct/combined roles of IR and IGF1R. Analyses focused on the impact of these deletions on hepatic steatosis and metabolism, whole-body adiposity, and liver tumor incidence. Results: IR and IGF1R signaling contribute to steatosis induced by Pten ablation through distinct mechanisms. Hepatic IGF1R regulates hepatic glucose output and glycogen storage (2.1-fold increase in hepatic glycogen in PTEN-IGF1RKO mice [n = 10], compared with PTENKO mice [n = 7], p <0.0001). In contrast, hepatic IR exerts a stringent regulation on whole-body adiposity (4-fold increase in white adipose tissue volume in PTEN-IRKO mice [n = 5], compared with PTENKO mice [n = 6], p = 0.0004). Interestingly, triple knockout (Insr, Igf1r, and Pten) in hepatocytes of young adult mice is largely asymptomatic, indicating that PTEN deficiency exerts a major overriding control on the effects of Insr and Igf1r deletion. Furthermore, the combined loss of IR and IGF1R signaling in PTEN-deficient livers restrains liver carcinogenesis, but both receptors have individually distinct effects on the malignancy of liver cancers, with IR deficiency reducing overall cancer incidence and IGF1R deficiency promoting malignancy. Conclusions: These findings increase our understanding of the intricate interplay between PTEN, IR, and IGF1R signaling and provide valuable insights into potential therapeutic interventions in hepatic disorders and hepatocellular carcinoma. Impact and implications:: This study underscores the pivotal roles of phosphatase and tensin homolog (PTEN), insulin receptor (IR), and IGF-1 receptor (IGF1R) in controlling liver metabolism, systemic adiposity, and liver cancer progression. Our findings on the distinct and combined effects of these receptors in PTEN-deficient mice offer key insights into the mechanisms driving metabolic dysfunction-associated steatotic liver disease and related hepatocarcinogenesis. In addition, this research reveals the potential of IR and IGF1R as biomarkers in liver cancer development, presenting new opportunities for therapeutic targeting and disease monitoring.